Methods of Improving the Technical and Tactical Movements of Highly Qualified Greco-Roman Wrestlers - Tursunov Shukhrat Sabitjonovich (Zien Journals, 2022)
In the article, the main objectives were to identify and record effective and evaluated technical and tactical actions in a competitive duel according to Greco-Roman wrestling rules.
Keywords: physical development; technical and tactical training